1998
DOI: 10.3109/07435809809032678
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel secretogranin II-derived peptide in the adult and fetal human adrenal gland

Abstract: Molecular cloning of secretogranin II (SgII) in different species has revealed the existence of a highly conserved 66-amino acid peptide (EM66) flanked by preserved pairs of basic residues. In the present study we have localized and characterized EM66 in the human adrenal gland. A fusion protein containing the human EM66 peptide was produced in E. coli and used to raise polyclonal antibodies in rabbits. Immunohistochemical staining of human adrenal slices revealed intense labeling of adrenochromaffin cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…EM66 was named according to its length (66 amino acids) and its N-and C-terminal glutamic acid and methionine residues, respectively, in the human sequence. [10][11][12][13][14][15][16] EM66 was initially characterised in the human adrenal gland, in gonadotrophs and lactotrophs of the rat pituitary, and in specific rodent hypothalamic nuclei, suggesting that, upon stimulation, EM66 may be released to act as an autocrine, paracrine and/or endocrine factor. 17,18 Clinically, it has been shown that EM66 is present in tumoural chromaffin cells and represents a sensitive diagnostic and pronostic marker of pheochromocytoma.…”
Section: Introductionmentioning
confidence: 99%
“…EM66 was named according to its length (66 amino acids) and its N-and C-terminal glutamic acid and methionine residues, respectively, in the human sequence. [10][11][12][13][14][15][16] EM66 was initially characterised in the human adrenal gland, in gonadotrophs and lactotrophs of the rat pituitary, and in specific rodent hypothalamic nuclei, suggesting that, upon stimulation, EM66 may be released to act as an autocrine, paracrine and/or endocrine factor. 17,18 Clinically, it has been shown that EM66 is present in tumoural chromaffin cells and represents a sensitive diagnostic and pronostic marker of pheochromocytoma.…”
Section: Introductionmentioning
confidence: 99%
“…It is speculated that this difference is due to the presence of a functional cAMP response element in the promoter of the SgII gene. 2 Furthermore, SgII has been known to produce functionally active neurotrophic or angiogenic peptides such as secretoneurin, 11,12,[15][16][17]56 EM66, [57][58][59] and manserin 60,61 through the processing of its precursor protein. 62 However, the SgIII precursor protein does not produce active peptides, 3 despite undergoing similar proteolytic processing of the precursor protein.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous cleavage sites are consistent with the specificity of prohormone convertases (PC1/3 and PC2) and carboxypeptidase E (CPE), that reside within chromaffin granules (Metz-Boutigue et al, 1993;Seidah & Chretien 1999). Secretogranin II (SgII), the third member of the chromogranin family is also processed to generate several natural fragments (Metz-Boutigue et al, 1993;Anouar et al, 1998;Marksteiner et al, 1993;Yajima et al, 2004). The discovery that pancreastatin, a chromogranin A (CGA)-derived peptide inhibits insulin secretion from pancreatic beta-cells, initiated the concept of prohormone (Eiden, 1987;tatemoto et al, 1986).…”
Section: Introductionmentioning
confidence: 93%